Immunomodulatory effects of probiotics isolated from traditional fermented foods and beverages of Sumatra (Indonesia) and synbiotics in mice - NUR INDAH PERMATASARI HARAHAP; ERMAN MUNIR; SALOMO HUTAHAEAN (Society for Indonesian Biodiversity, 2023)
Abstract. Harahap NIP, Munir E, Hutahaean S. 2023. Immunomodulatory effects of probiotics isolated from traditional fermented foods and beverages of Sumatra (Indonesia) and synbiotics in mice. Biodiversitas 24: 1157-1162. Traditional Sumatran foods and beverages such as sugar palm sap, dadih, and tempoyak have a higher nutritional value than the original ingredients. Lactic Acid Bacteria (LAB), a group of gut bacteria, is the starter that commonly appeared abundantly during fermentation of these natural products. Probiotics are microorganisms that, when consumed in sufficient amounts, provide health benefits to the host, one of which is immunomodulation. When probiotics are coupled with prebiotics to create a unified product known as synbiotics, their function as immunomodulators improves. The goal of this study is to identify new probiotic candidate LAB strains from traditional Sumatran fermented products in combination with inulin as a prebiotic, that can act as immunomodulators in mice through phagocytosis activity. Eight bacterial isolates encoded as NI01, NI02, NI04, DA01, DA02, TE01, TE02 and TE03 were isolated as LAB strains. Four isolates i.e. NI02, NI04, DA01, and TE02 were identified molecularly as Lactiplantibacillus plantarum, Leuconostoc mesenteroides, Lacticaseibacillus paracasei and Lactiplantibacillus plantarum, respectively which were antagonists to human pathogenic bacteria, Escherichia coli and Staphylococcus aureus. The highest phagocytic activity of macrophages was observed through the administration of synbiotics from DA01 + Inulin at 98%, followed by TE02 (96%), NI04 (95%), and NI02 (92%). The findings of this study demonstrated the potential of LAB strains in traditional fermented Sumatran products as probiotic agents and immunomodulators for future application in the health sector.